2022
DOI: 10.3390/socsci11100490
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Interventions for the Prevention and Control of Cutaneous Leishmaniasis: A Systematic Review

Abstract: We reviewed the evidence on community-based interventions for the prevention and control of cutaneous leishmaniasis (CL). Community initiatives tailored towards awareness and mobilisation are regarded as a priority area in the Neglected Tropical Disease Roadmap 2021–2030 by the World Health Organization. We searched nine electronic databases for intervention-based studies. Two independent reviewers screened and assessed the articles for methodological quality using predefined criteria. We conducted a meta-anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…A review of community interventions found that education and innovative approaches targeting stigma, financial barriers, and access to healthcare can improve knowledge, attitudes, and practices in communities. (13).…”
Section: Discussionmentioning
confidence: 99%
“…A review of community interventions found that education and innovative approaches targeting stigma, financial barriers, and access to healthcare can improve knowledge, attitudes, and practices in communities. (13).…”
Section: Discussionmentioning
confidence: 99%